Implementation of graywater reuse in the State of Colorado - Vandegrift, Jillian, author; Sharvelle, Sybil, advisor; Glick, Scott, committee member; Grigg, Neil, committee member (Colorado State University. Libraries, 2014)
The United States is expected to see large population growth in the coming years. The southwest region of the country will see dramatic effects due to a higher demand for water paired with concerns associated with climate change resulting in less runoff, increased temperatures and evapotranspiration, and decreased precipitation (Barnett et al. 2007). Water conserving methods such as low-flow fixtures and appliances are believed to be approaching their maximum water saving potential and new techniques are needed in order to protect the world's most valuable resource. Graywater reuse is a strategy gaining popularity because it is a low-strength wastewater that is easier and less expensive to treat than domestic wastewater (Winward et al 2008). Graywater, or water discharged from showers, bathtubs, laundry machines, and laundry and bathroom faucets, constitutes approximately 44% of total indoor water use at the household level (REUWS, 2012). The reuse of graywater for toilet flushing and irrigation has been well studied at the household level, however little research has been done regarding water reuse at commercial facilities. Through a series of feasibility studies, water use at several business types was investigated in order to identify facilities that could benefit from simple water reuse methods. Conclusions from these studies show that research labs, hotels, and gyms have the potential to reduce their demand on municipal water by up to 21%. Overall, businesses that have balanced water use tendencies between graywater demand and graywater supply resulted in the largest estimated potential water savings. In contrast, businesses such as office buildings do not typically generate large amounts of graywater and therefore are not often ideal candidates for graywater reuse, unless there is on-site laundry effluent available for reuse. Water conservation also has its downfalls in terms of implementation. In the western region of the United States, water allocations and water rights are a serious consideration for municipalities. The City of Fort Collins Utilities was interested in investigating the potential impacts to return flows associated with graywater reuse. Adoption of graywater reuse in existing, and new and redevelopment populations in Fort Collins was estimated to be between 5-10%, and 80-100%, respectively. Results of the impact to return flows study show the City of Fort Collins could see a maximum reduction in return flows of 5.5% in realistic adoption rate scenarios. In hypothetical adoption rate scenarios, calculations were made in order to capture the effects of 100% adoption in existing, new and redevelopment areas of Fort Collins. Though this adoption rate is highly improbable, it illustrates the potential impacts that newer developing cities may see if graywater reuse is integrated as part of the infrastructure planning process. 100% adoption of graywater reuse resulted in an estimated 21% reduction from base flows to the wastewater treatment plant. Additionally, implementation of graywater reuse will be dependent upon city/county local ordinances when Regulation 86 is finalized in the future. In order to assist the development of a city ordinance for Fort Collins, as well as promote graywater reuse, a series of Best Management Practices documents and graywater factsheets were created with educational intentions. Recommendations for design criteria and permit requirements were provided in another series of documents attached in the appendices of this report. Operational experience was beneficial in terms of making the appropriate design criteria recommendations for graywater legislation. The graywater reuse system for toilet flushing at Aspen Residence Hall on Colorado State University's campus provided several valuable operational experiences when it underwent the first actual implementation period in the spring of 2014. The first operational period was generally successful aside from a few instances of unexpected malfunctions and equipment failures resulting in foul odors in student's toilets. Automatic chlorine residual monitoring was utilized in order to protect public health, and chlorine residuals were present during unexpected occurrences. Student survey results show mixed feelings towards the graywater reuse system, however most negativity was attributed to the isolated malfunction incidents and not normal operation periods. The fall of 2014 will serve as another pilot-phase period in which necessary system improvements will be made prior to start-up, and more frequent monitoring of chlorine residuals in student's toilet will occur in order to better gauge the functionality of the system.
Keywords: water reuse; water; graywater; reuse